Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Flocculation of dimorphic yeast benjaminiella poitrasii is altered by modulation of NAD-glutamate dehydrogenase - Joshi, C. V.; Ghormade, Vandana; Kunde, P.; Kulkarni, P.; Mamgain, H.; Bhat, Suresh K.; Paknikar, K. M.; Deshpande, Mukund V. (Bioresource Technology, 2010)
A strategy to control flocculation is investigated using dimorphic yeast, Benjaminiella poitrasii as a model. Parent form of this yeast (Y) exhibited faster flocculation (11.1 min) than the monomorphic yeast form mutant Y-5 (12.6 min). Atomic force microscopy revealed higher surface roughness of Y (439.34 rms) than Y-5 (52 rms). Also, the former had a zeta potential of -65.97 +/- 3.45 as against -50.21 +/- 2.49 for the latter. Flocculation of both Y and Y-5 could be altered by supplementing either substrates or inhibitor of NAD-glutamate dehydrogenase (NAD-GDH) in the growth media. The rate of flocculation was promoted by alpha-ketoglutarate or isophthalic acid and decelerated by glutamate with a statistically significant inverse correlation to corresponding NAD-GDH levels. These interesting findings open up new possibilities of using NAD-GDH modulating agents to control flocculation in fermentations for easier downstream processing. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Benjaminiella poitrasii; dimorphism; flocculation; NAD-glutamate dehydrogenase

Phase behavior of lipid-based lyotropic liquid crystals in presence of colloidal nanoparticles - Venugopal, Edakkal; Bhat, Suresh K.; Vallooran, Jijo J.; Mezzenga, Raffaele (Langmuir, 2011)
We have investigated the microstructure and phase behavior of monoglyceride-based lyotropic liquid crystals in the presence of hydrophilic silica colloidal particles of size comparable to or slightly exceeding the repeat units of the different liquid crystalline phases. Using small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC), we compare the structural properties of the neat mesophases with those of the systems containing silica colloidal particles. It is found that the colloidal particles always macrophase separate in inverse bicontinuous cubic phases of gyroid (Ia3d) and double diamond (Pn3m) symmetries. SAXS data for the inverse columnar hexagonal phase (H(II)) and lamellar phase (L(alpha)) suggest that a low volume fraction of the nanoparticles can be accommodated within the mesophases, but that at concentrations above a given threshold, the particles do macrophase separate also in these systems. The behavior is interpreted in terms of the enthalpic and entropic interactions of the nanoparticles with the lamellar and hexagonal phases, and we propose that, in the low concentration limit, the nanoparticles are acting as point defects within the mesophases and, upon further increase in concentration, initiate nucleation of nanoparticles dusters, leading to a macroscopic phase separation.

Microstructural elucidation of self-emulsifying system: effect of chemical structure - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2012)
Self-emulsifying systems (SES) emulsify spontaneously to produce fine oil-in-water emulsion when introduced into aqueous phase. The self-emulsification process plays an important role during formation of emulsion. The objective of current work was to understand and explore the inner structuration of SES through controlled hydration and further to study the influence of additive on the same which ultimately governs performance of final formulation in terms of droplet size. Droplet size of final formulations containing structural analogues of ibuprofen was determined. Microstructural properties of intermediate hydrated regimes of SES were investigated using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. The current work established inverse relationship between droplet size of the formulations containing structural analogues of ibuprofen and their Log P values. Microstructural analysis of intermediate hydrated regimes of the prepared samples showed formation of local lamellar structure. Structural analogues of ibuprofen significantly altered microstructure of lamellae which was well correlated with the droplet size of final formulations. In vitro drug release study showed increase in dissolution rate of lipophillic drugs when formulated as SES. The current work emphasizes the fact that tailor-made formulations can be prepared by controlling the properties of intermediate regimes.
Keywords: emulsion; flurbiprofen; ibuprofen; ketoprofen; lamellar structure; self-emulsifying system; structural analogues

Probing influence of mesophasic transformation on performance of self-emulsifying system: effect of ion - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Molecular Pharmaceutics, 2012)
Self-emulsifying systems are mixtures of oils and surfactants, ideally isotropic, sometimes including cosolvents, which emulsify under conditions of gentle agitation, similar to those which would be encountered in the gastrointestinal tract. The process of self-emulsification has remained the center of attraction for most researchers. Controlled hydration of self-emulsifying systems shows formation of an intermediate gel phase which upon rupture forms an emulsion. Current work was undertaken to understand and explore the microstructural properties of intermediate gel phase which are believed to influence the performance (droplet size) of the final formulation. The effect of additives on microstructural properties of intermediate gel phase has also been investigated. Microstructural elucidation of hydrated samples of intermediate regimes was done by using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. Samples from intermediate regimes showed formation of local lamellar structure which swelled with hydration. In the present work, the effect of addition of salt form of naproxen (sodium and potassium) and naproxen (base) on microstructural properties of intermediate regimes was investigated. Systems containing naproxen salts formed larger droplets whereas naproxen base formed smaller ones. Microstructural properties of intermediate lamellar structures were well correlated with performance of the final formulation. The current studies indicate that by controlling the properties of intermediate regimes optimized formulations with desired performance can be tailor-made.
Keywords: emulsion; lamellar structure; liquid crystal; Microstructure; Naproxen; self-emulsifying system

Mapping ion-induced mesophasic transformation in lyotropic in situ gelling system and its correlation with pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2013)
To investigate influence of ion induced mesophasic transformation on pharmaceutical performance of in situ gelling system consisting of glyceryl monooleate. The prepared system showed mesophasic transformation during its conversion from sol to gel upon controlled hydration. The process of mesophasic transformation was studied by SAXS, DSC, rheology and plane polarized light microscopy. Further the influence of additives i.e. naproxen salts (sodium and potassium) and naproxen (base) on the process of mesophasic transformation was also elucidated. It was observed that addition of salt form of naproxen transformed W/O emulsions into cubic mesophase whereas addition of base form of naproxen formed reverse hexagonal (H-II) phase upon controlled hydration. The cubic mesophase formed by naproxen salts retarded the drug release for initial 3 h whereas H-II phase showed sustained drug release characteristics for naproxen base following Higuchi drug release kinetics. The current work suggests that formulations with tailor made pharmaceutical performance can be developed by selecting proper additives in the system so as to obtain the desired mesophase `on demand' thereby controlling drug release characteristics.
Keywords: cubic phase; hexagonal phase; liquid crystal; mesophasic transformation; sustained drug release

Exploring microstructural changes in structural analogues of ibuprofen-hosted in situ gelling system and its influence on pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (AAPS Pharmscitech, 2015)
The present work explores inner structuration of in situ gelling system consisting of glyceryl monooleate (GMO) and oleic acid (OA). The system under study involves investigation of microstructural changes which are believed to govern the pharmaceutical performance of final formulation. The changes which are often termed mesophasic transformation were analysed by small angle Xray scattering (SAXS), differential scanning calorimetry (DSC), rheology and plane polarised light (PPL) microscopy. The current work revealed transformation of blank system from W/O emulsion to reverse hexagonal structure upon addition of structural analogues of ibuprofen. Such transformations are believed to occur due to increased hydrophobic volume within system as probed by SAXS analysis. The findings of SAXS studies were well supported by DSC, rheology and PPL microscopy. The study established inverse relationship between log P value of structural analogues of ibuprofen and the degree of binding of water molecules to surfactant chains. Such relationship had pronounced effect on sol-gel transformation process. The prepared in situ gelling system showed sustained drug release which followed Higuchi model.
Keywords: flurbiprofen; hexagonal phase; ibuprofen; ketoprofen; liquid crystal; sustained drug release

Micro-structural analysis of NiFe2O4 nanoparticles synthesized by thermal plasma route and its suitability for BSA adsorption - Bhosale, Shivaji V.; Kanhe, Nilesh S.; Bhoraskar, S. V.; Bhat, Suresh K.; Bulakhe, Ravindra N.; Shim, Jae-Jin; Mathe, Vikas L. (Journal of Materials Science-Materials in Medicine, 2015)
The paper presents the experimental studies pertaining to the adsorption of bovine serum albumin (BSA) on the nanoparticles of nickel ferrite (NiFe2O4) with a view of correlating the adsorption properties to their microstructure and zeta potentials. Physical properties of two kinds of nickel ferrites, one synthesized by thermal plasma route and the other by chemical co-precipitation method, are compared. Maximum adsorption (231.57 lg/mg) of BSA onto nickel ferrite nanoparticles, at body temperature (37 degrees C) was observed at pH-value of 5.58 for the thermal plasma synthesized particles showing its higher adsorption capacity than those synthesized by wet chemical means (178.71 mu g/mg). Under the same physical conditions the value of zeta potential, obtained for the former, was higher than that of the latter over a wide range of pH values (3.64-9.66). This is attributed to the differences in the specific surface energies of the two kinds of nanoparticles arising from the degree of crystallinity. The paper presents the experimental evidence for the single crystalline nature of the individual nanoparticles, with mean size of 32 nm, for the thermal plasma synthesized particles as evidenced from the high resolution transmission electron microscopy and electron diffraction analysis. The measurements also reveal the poor crystalline morphology in the chemically prepared particles (mean size of 28 nm) although the X-ray diffraction patterns are not much different. The atomic force microscopy images confirm that the surfaces of plasma synthesized nanoparticles possesses higher surface roughness than that of chemically synthesized one. Presence of adsorbed protein was confirmed by vibrational spectroscopy. The Langmuir adsorption model is found to fit into the experimental data better than the Freundlich adsorption model.

Template -free assembly in living bacterial suspension under an external electric field - Samantaray, Kunal; Bhol, Prachi; Sahoo, Bhaban; Barik, Subrat Kumar; Jathavedan, Kiran; Sahu, Bikash Ranjan; Bikash Ranjan; Suar, Mrutyunjay; Bhat, Suresh K.; Mohanty, Priti Sunda (ACS Omega, 2017)
Although template-assisted self-assembly methods are very popular in materials and biological systems, they have certain limitations such as lack of tunability and switchable functionality because of the irreversible association of cells and their matrix components. With an aim to achieve more tunability, we have made an attempt to investigate the self-assembly behavior of rod-shaped living bacteria subjected to an external alternating electric field using confocal microscopy. We demonstrate that rod-shaped living bacteria dispersed in a low salinity aqueous medium form different types of reversible freely suspended structures when subjected to an external alternating electric field. At low field strength, an oriented phase is observed where individual bacterium orients with its major axis aligned along the field direction. At intermediate field strength, bacteria align in the form of one-dimensional (1D) chains that lie along the field direction. Further, at high field strength, more bacteria associate with these 1D chains laterally to form a two-dimensional (2D) array. At higher bacterial concentration, these field-induced 2D arrays extend to form three-dimensional columnar structures. These results are discussed in the context of previously reported studies on bacterial self-assembly.
Keywords: Bacteria; Electric Properties; Self- Assembly

Thermo-responsive PNIPAM-metal hybrids: an efficient nanocatalyst for the reduction of 4-nitrophenol - Satapathy, Smith Sagar; Bhol, Prachi; Chakkarambath, Aswathy; Mohanta, Jagdeep; Samantaray, Kunal; Bhat, Suresh K.; Panda, Subhendu K.; Mohanty, Priti S.; Si, Satyabrata (Applied Surface Science, 2017)
Micron size thermoresponsive cross-linked polymeric microgels of poly(N-isopropylacrylamide) (PNIPAM) are used as "microreactor" for embedding metal nanoparticles of different shapes. Using a simple and robust method, we have synthesized various polymer-metal hybrid nanostructures incorporated with Au nanorods (AuNR), Au nanospheres (AuNS) and Ag nanospheres (AgNS). These hybrid nanostructures have been characterized by transmission electron microscope (TEM), UV-vis spectroscopy, dynamic light scattering (DLS) and static light scattering (SLS) followed by their catalytic activity. TEM studies directly confirmed the mondispersity of synthesized hybrid microgels and stability of the embedded metal nanoparticles within the microgels. Optical studies confirmed the presence of respective absorption bands that correspond to AuNS, AgNS and AuNR respectively. Extensive DLS studies demonstrated that although these hybrid microgels preserve their thermoresponsive properties, i.e their hydrodynamic radius decreased with increasing temperature, their thermosensitivity were comparatively lesser than pure PNIPAM microgels. Combining with studies using static light scattering, we further found that AuNS and AgNS were inhomogeneously distributed within microgels where the majority of the nanoparticles present within the loosely cross-linked shell. On the other hand AuNR were distributed more homogeneously within the microgels. Catalytic performance of various nanostructures loaded onto PNIPAM microgel beads were evaluated by studying the catalytic reduction of 4-nitrophenol. Complete catalytic conversion using AgNS occurred in similar to 30 min with a first-order rate constant of 0.159 min(-1) having a 7 min induction period. On the other hand no induction period was observed for AuNS and AuNR and the reaction completed in 3-4 min with a first-order rate constant of 1.607 min(-1) and 1.627 min(-1) respectively. Further, PNIPAM-AuNS and PNIPAM-AuNR possess better catalytic activity as well as recyclability compared to that of PNIPAM-AgNS. (C) 2017 Elsevier B.V. All rights reserved.

Controlled surface/interface structure and spin enabled superior properties and biocompatibility of cobalt ferrite nanoparticles - Ansari, Sumayya M.; Sinha, Bhavesh B.; Pai, Kalpana R.; Bhat, Suresh K.; Ma, Yuan-Ron; Sen, Debasis; Kolekar, Yesh D.; Ramana, C., V. (Allied Surface Science, 2018)
High quality, crystalline, well-dispersed, and stable magnetic oxide nanoparticles (NPs) of inverse spinel cobalt ferrite (CoFe2O4; CFO) were prepared by a facile, reproducible, and simple hydrothermal route. The transmission electron microscopy, small-angle scattering and X-ray diffraction analyses demonstrate the structural quality of CFO NPs with a controlled size of similar to 12 nm. Small-angle scattering experiments demonstrate that the pristine CFO NPs have the individual size similar to 8.5 nm and spherical shape. The Raman and infrared spectroscopic measurements further confirm their high chemical quality and cubic symmetry. CFO NPs exhibit a remarkable, maximum coercivity (H-c) value of 18.92 kOe, which is the highest value achieved to date. Surface spins and spins canting along with a weak dipolar interaction accounts for the giant H-c and large effective anisotropy (11.45 x 10(6) erg/cm(3)) of these CFO NPs. The magnetic grain size of NPs reveals that the canted surface spins exist around the magnetic particles. Reorientation of surface spins and interparticle interaction causes the jumping behaviour in M-H hysteresis loops at H = 0. The cell viability of CFO NPs against the cancer (cisplatin resistant ovarian cancer - A2780/CP70) was evaluated to determine their potential application in biomedicine and health science. The mild response of CFO NPs in terms of their anti-proliferative nature against cancer cells and negligible cytotoxicity suggests their human-safe-and-friendly nature which makes them suitable for biomedical/health-related applications. Assessment of toxicity toward human red blood cells (RBC) revealed that hemolysis is less than 5% compared to the positive control confirming the potential applications of CFO NPs targeting human cells and making relevant for adopting them in biomedicine.

Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation

Alternating electric-field-induced assembly of binary mixtures of soft repulsive ionic microgel colloids - Jathavedan, Kiran; Bhat, Suresh K.; Mohanty, Priti S. (Journal of Colloid and Interface Science, 2019)
An external alternating electric field is used to study the assembly of a binary mixture of Poly(N-isopro pylacrylamide-co-acrylic acid) microgels in their swollen form at hydrodynamic size ratio 2:1 under deprotonated state. The AC field experiments were carried out at a fixed frequency of 100 kHz in the fluid regime for three number density ratios 1:3, 1:1 and 3:1 of big-to-small microgels using a confocal microscope. Strings with different types of co-assembly structures such as buckled, ring, flame and sandwich have been observed at low and intermediate field strengths at ratio 1:3, 1:1. In buckled and ring type, one or two small particles sit at the contact of two big particles and in the flame type, small particles arrange like a cone at end of the string. In the sandwich structure, several double small particle layers lie in between big particles. At high field strength, aggregation of strings and a phase separation into individual aggregates of strings from both big and small microgels have been observed. At higher ratio 3:1, the string formation is mostly dominated by big particles. Our experimental results are discussed with the recent simulation and experimental works on AC field induced structures in binary hard sphere mixtures. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: assembly; dipolar interactions; Microgels; Soft colloids

Hierarchical nanoflower arrays of Co9S8-Ni3S2 on nickel foam: a highly efficient binder-free electrocatalyst for overall water splitting - Illathvalappil, Rajith; Walko, Priyanka S.; Kanheerampockil, Fayis; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Chemistry-A European Journal, 2020)
Hydrogen production is vital for meeting future energy demands and managing environmental sustainability. Electrolysis of water is considered as the suitable method for H-2 generation in a carbon-free pathway. Herein, the synthesis of highly efficient Co9S8-Ni3S2 based hierarchical nanoflower arrays on nickel foam (NF) is explored through the one-pot hydrothermal method (Co9S8-Ni3S2/NF) for overall water splitting applications. The nanoflower arrays are self-supported on the NF without any binder, possessing the required porosity and structural characteristics. The obtained Co9S8-Ni3S2/NF displays high hydrogen evolution reaction (HER), as well as oxygen evolution reaction (OER), activities in 1 m KOH solution. The overpotentials exhibited by this system at 25 mA cm(-2) are nearly 277 and 102 mV for HER and OER, respectively, in 1 m KOH solution. Subsequently, the overall water splitting was performed in 1 m KOH solution by employing Co9S8-Ni3S2/NF as both the anode and cathode, where the system required only 1.49, 1.60, and 1.69 V to deliver the current densities of 10, 25, and 50 mA cm(-2), respectively. Comparison of the activity of Co9S8-Ni3S2/NF with the state-of-the-art Pt/C and RuO2 coated on NF displays an enhanced performance for Co9S8-Ni3S2/NF both in the half-cell as well as in the full cell, emphasizing the significance of the present work. The post analysis of the material after water electrolysis confirms that the surface Co(OH)(2) formed during the course of the reaction serves as the favorable active sites. Overall, the activity modulation achieved in the present case is attributed to the presence of the open-pore morphology of the as formed nanoflowers of Co9S8-Ni3S2 on NF and the simultaneous presence of the surface Co(OH)(2) along with the highly conducting Co9S8-Ni3S2 core, which facilitates the adsorption of the reactants and subsequently its conversion into the gaseous products during water electrolysis.
Keywords: cobalt sulfide; electrocatalysts; Hydrogen evolution; overall water splitting; oxygen evolution

Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.